2015
DOI: 10.2749/222137815818357953
|View full text |Cite
|
Sign up to set email alerts
|

Report of an Unexpected Vortex-Induced Vibration in an Actual Suspension Bridge

Abstract: An unexpected vibration was observed on the Yi Sun-sin Bridge on October 26th, 2014. Since the bridge was subjected to a single mode vibration in limited amplitude for one and half hours, it was regarded as a vortex-induced vibration (VIV). Since the bridge was aerodynamically well designed for the VIV as well as flutter instability, the cause of the vibration was investigated via a series of two-dimensional wind tunnel tests. The one-side lanes were closed to traffics and the epoxycoated wearing surface was b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Among the plant phenolics tested in Supplementary Table 1, targeted assays have discovered DNA gyrase inhibitory activity for 11 phenolic compounds (Ohemeng et al, 1993; Wu et al, 2013b), type III secretion inhibition for 9 compounds (Tsou et al, 2016), inhibition of helicase activity for 5 phenolic compounds (Xu et al, 2001), multi-drug efflux pump inhibitors for 3 compounds (Smith et al, 2007; Fiamegos et al, 2011; Bag and Chattopadhyay, 2014), dehydratase inhibition for 3 compounds (Zhang et al, 2008), protein kinase inhibition for 2 compounds (Shakya et al, 2011), and single phenolic compounds among which one inhibited urease activity (Moon et al, 2013), one bound iron (Chung et al, 1998), one inhibited succinate dehydrogenase and malate dehydrogenase (Yao et al, 2012), one intercalated into DNA (Lou et al, 2012), one induced DNA fragmentation, an ROS response, and suppressed FtsZ expression (Hwang and Lim, 2015), and one bound to the FtsZ protein and inhibited FtsZ assembly (Rai et al, 2008). Many of these results clearly come from large experimental activity screens in which several phenolic compounds were assessed for a single mechanism of action.…”
Section: Non-membrane Mechanisms Of Actionmentioning
confidence: 99%
“…Among the plant phenolics tested in Supplementary Table 1, targeted assays have discovered DNA gyrase inhibitory activity for 11 phenolic compounds (Ohemeng et al, 1993; Wu et al, 2013b), type III secretion inhibition for 9 compounds (Tsou et al, 2016), inhibition of helicase activity for 5 phenolic compounds (Xu et al, 2001), multi-drug efflux pump inhibitors for 3 compounds (Smith et al, 2007; Fiamegos et al, 2011; Bag and Chattopadhyay, 2014), dehydratase inhibition for 3 compounds (Zhang et al, 2008), protein kinase inhibition for 2 compounds (Shakya et al, 2011), and single phenolic compounds among which one inhibited urease activity (Moon et al, 2013), one bound iron (Chung et al, 1998), one inhibited succinate dehydrogenase and malate dehydrogenase (Yao et al, 2012), one intercalated into DNA (Lou et al, 2012), one induced DNA fragmentation, an ROS response, and suppressed FtsZ expression (Hwang and Lim, 2015), and one bound to the FtsZ protein and inhibited FtsZ assembly (Rai et al, 2008). Many of these results clearly come from large experimental activity screens in which several phenolic compounds were assessed for a single mechanism of action.…”
Section: Non-membrane Mechanisms Of Actionmentioning
confidence: 99%
“…In 2020, significant vortex vibrations with amplitudes ranging from 0.1 m to 0.3 m were observed on the Humen suspension bridge in China [10]. Other examples of VIV occurrences on real bridges include the Xihoumen Bridge [6] and Yingwuzhou Yangtze River Bridge [11] in China, as well as the Yi Sun-sin Bridge in Korea [12]. Investigations revealed that, despite the short duration of these conditions, several drivers experienced different levels of short-term physical discomfort [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, many concrete bridges are in poor condition as soon as after 20 to 30 years of service and cannot achieve designed service life without complex and expensive repairs due to the structural and material degradation [3]. The causes of bridge deterioration and shortening of its service life are: errors and negligence during design, poor construction quality, lack of maintenance, degradation mechanism caused by aggressive environment, increasing service load and hazards, and very often a combination of several of the aforementioned causes [4][5][6][7][8][9][10][11][12][13][14][15]. Corrosion of embedded reinforcement is the most prevalent form of degradation of reinforced concrete (RC) structures, especially bridges exposed to the sea and/or de-icing salts.…”
Section: Introductionmentioning
confidence: 99%